Detection of Cocoa Pod Borer Infestation Using Sex Pheromone Trap and its Control by Pod Wrapping - Dian Rahmawati; Fransiscus Xaverius Wagiman; Tri Harjaka; Nugroho Susetya Putra (Jurnal Perlindungan Tanaman Indonesia, 2017)
Cocoa pod borer (CPB), Conopomorpha cramerella Snellen (Lepidoptera: Gracillariidae) is a major pest of cocoa. Detection of the pest infestation using sex pheromone traps in the early growth and development of cocoa pods is important for an early warning system programme. In order to prevent the pest infestation the young pods were wrapped with plastic bags. A research to study the CPB incidence was conducted at cocoa plantations in Banjarharjo and Banjaroya villages, District of Kalibawang; Hargotirto and Hargowilis villages, District of Kokap; and Pagerharjo village, District of Samigaluh, Yogyakarta. The experiments design used RCBD with four treatments (sex pheromone trap, combination of sex pheromone trap and pod wrapping, pod wrapping, and control) and five replications. As many as 6 units/ha pheromone traps were installed with a distance of 40 m in between. Results showed that one month prior to the trap installation in the experimental plots there were ripen cocoa pods as many as 9-13%, which were mostly infested by CPB. During the time period of introducting research on August to Desember 2016 there was not rambutan fruits as the CPB host, hence the CPB resource was from infested cocoa pods. The CPB moth trapped as many as 0−7 (1.13 ± 0.14) moths/6 traps/12 observations. The seed damage due to CPB larvae in the pheromone trap treatments (23.98%) was relatively similar with the control (20.25%). Seed damage rate in combination treatment of pheromone trap and pod wrapping (0.59%) was relatively the same with the pod wrapping (0.20%). The pheromone trap was more usefull for monitoring tool rather than for control, meanwhile pod wrapping was an effective control measure of CPB. IntisariPenggerek Buah Kakao (PBK), Conopomorpha cramerella Snellen (Lepidoptera: Gracillariidae) merupakan salah satu hama utama kakao. Deteksi serangan hama PBK dengan perangkap feromon seks pada awal pertumbuhan dan perkembangan buah kakao penting dilakukan sebagai sistem peringatan dini. Dalam upaya pencegahan serangan hama tersebut dilakukan pembrongsongan buah muda. Penelitian dilakukan di kebun kakao rakyat di Desa Banjarharjo dan Banjaroya, Kecamatan Kalibawang, Desa Hargotirto dan Hargowilis, Kecamatan Kokap, serta kebun PT Pagilaran di Desa Pagerharjo, Kecamatan Samigaluh, Yogyakarta. Percobaan dengan empat perlakuan (perangkap feromon, kombinasi perangkap feromon dan brongsong, brongsong, kontrol) dan lima ulangan menggunakan rancangan RCBD. Perangkap feromon sebanyak 6 unit/ha dipasang dengan jarak antar perangkap sekitar 40 m. Hasil percobaan menunjukkan bahwa satu bulan sebelum pemasangan perangkap terdapat buah tua sebanyak 9−13 % dan umumnya terserang PBK. Selama kajian berlangsung tidak terdapat buah rambutan sebagai inang PBK sehingga sumber PBK diduga hanya dari buah kakao yang terserang. Ngengat PBK yang tertangkap yaitu sebanyak 0−7 (1,13±0,14) ekor/6 perangkap/12 pengamatan. Intensitas kerusakan biji akibat ulat PBK pada perlakuan perangkap feromon (23,98%) relatif sama dengan kontrol (20,25%). Kerusakan biji kakao pada perlakuan kombinasi perangkap feromon dan pembrongsongan (0,59%) relatif sama dengan pembrongsongan saja (0,20%). Perangkap feromon lebih berfungsi sebagai alat monitoring daripada alat pengendalian PBK, sedangkan pembrongsongan buah merupakan teknologi pengendalian PBK yang efektif.